1997
DOI: 10.1093/jn/127.10.2024
|View full text |Cite
|
Sign up to set email alerts
|

Delaying Colostrum Intake by One Day Impairs Plasma Lipid, Essential Fatty Acid, Carotene, Retinol and α-Tocopherol Status in Neonatal Calves , ,

Abstract: To study whether a delayed start of colostrum feeding in calves affects plasma lipids, fatty acids and fat-soluble vitamins, one group was fed colostrum (milkings 1-4) on d 1 and 2, then mature milk up to d 7, whereas two other groups were fed glucose or water on d 1, colostrum (milkings 1-4) on d 2 and 3 and then mature milk up to d 7. In calves fed colostrum on d 1, starting 5-7 h after birth, plasma concentrations of triglycerides, phospholipids, total cholesterol and of essential and nonessential fatty aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
58
2
3

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 15 publications
14
58
2
3
Order By: Relevance
“…when the animals still received whole milk. Similar to the studies by Blum et al (1997), the levels of total lipids, triglyceri des and phospholipids were lowest in the newborn calves. High concentrations of easily digestible components in the colostrum and in whole milk resulted in high lipid content in blood serum of calves aged 21 days.…”
Section: Resultssupporting
confidence: 84%
“…when the animals still received whole milk. Similar to the studies by Blum et al (1997), the levels of total lipids, triglyceri des and phospholipids were lowest in the newborn calves. High concentrations of easily digestible components in the colostrum and in whole milk resulted in high lipid content in blood serum of calves aged 21 days.…”
Section: Resultssupporting
confidence: 84%
“…In addition some authors have reported that a higher content of individual fatty acids in the first colostrum, such as C16:0 and C18:1 cis 9, may protect lambs from infection (Haug, Høstmatk, & Harstad, 2007;Isaacs, 2001;Pavlíková et al, 2010). This is consistent with findings of Blum, Hadorn, Sallmann, and Schuep (1997) who observed a higher incidence in infectious diseases connected to an insufficient intake of colostrum fatty acids.…”
Section: Resultssupporting
confidence: 70%
“…Plasma TG concentrations transiently increased in colostrum-fed calves during the first week of life, as shown previously [14,28,31], while in formula-fed calves TG concentrations remained low despite high fat intake. Together with lower phospholipid and cholesterol levels this indicates a reduced fat digestion and fatty acid absorption in formula-fed calves compared to colostrum-fed calves.…”
Section: Metabolic Traitssupporting
confidence: 83%